Study of the Effect of Various Drugs on Intestinal Microflora (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The anal canal of the rat rectum is morphologically subdivided into the pre-sphincter region, the transition zone, the internal sphincter, the external sphincter, the space between the sphincters and the intersphincter zone.When examining the internal and external sphincters of the rectum, it was revealed that they form a complex combined formation. Changes in the wall of the anal canal of the rectum depend on the type and duration of exposure to the xenobiotic and the age of the animals. Xenobiotics affect both their formation and function. The results obtained further reveal the mechanism of occurrence of various disorders of the sphincter apparatus of the rectum in areas with a high content of xenobiotics, in particular copper sulfate and potassium rhodanide.